The Failure of the Aetolian Deditio as a Didactic Cultural Clash in the Histories of Polybius (20.9-10) - Moreno Leoni, Álvaro Matías (2014)
This paper examines the Aetolian deditio in fidem of 191 as described by Polybius 20.9-10. Erich Gruen influentially interpreted Polybius’ description as inconsistent and exaggerated, on the grounds that Greeks and Romans from the 3rd and 2nd centuries BC had a common understanding of πίστις and fides and that Polybius’ own evidence on deditio was inconsistent. This paper reasserts the older view: that Greeks generally then had a hazy knowledge of Roman culture, including the practice of deditio, and that—even if weight be granted to factors such as the Roman commander’s personal character and ambitions or the historian’s supposed dislike of the Aetolians or his deployment of a degree of dramatic licence or a possible ‘hardening’ in the Romans’ general practice—this passage properly emphasises a genuine cultural clash, thereby promoting Polybius’ fundamental paideia-objective of teaching Greek readers, above all Greek politicians, how to respond competently to the realities of Roman power.